Genomic Signature Tags (GSTs): A System for Profiling Genomic DNA - Dunn, John J.; McCorkle, Sean R.; Praissman, Laura A.; Hind, Geoffrey; van der Lelie, Daniel; Bahou, Wadie F.; Gnatenko, Dmitri V.; Krause, Maureen K. (Genome Research, 2002)
Genomic signature tags (GSTs) are the products of a method we have developed for identifying and quantitatively analyzing genomic DNAs. The DNA is initially fragmented with a type II restriction enzyme. An oligonucleotide adaptor containing a recognition site forMmeI, a type IIS restriction enzyme, is then used to release 21-bp tags from fixed positions in the DNA relative to the sites recognized by the fragmenting enzyme. These tags are PCR-amplified, purified, concatenated, and then cloned and sequenced. The tag sequences and abundances are used to create a high-resolution GST sequence profile of the genomic DNA. GSTs are shown to be long enough for use as oligonucleotide primers to amplify adjacent segments of the DNA, which can then be sequenced to provide additional nucleotide information or used as probes to identify specific clones in metagenomic libraries. GST analysis of the 4.7-Mb Yersinia pestis EV766 genome using BamHI as the fragmenting enzyme and NlaIII as the tagging enzyme validated the precision of our approach. The GST profile predicts that this strain has several changes relative to the archetype CO92 strain, including deletion of a 57-kb region of the chromosome known to be an unstable pathogenicity island.[The following individuals kindly provided reagents, samples, or unpublished information as indicated in the paper: W. Crockett, K. Pellechi, J. Paparelli, J. Romeo, and K. Thompson.]
10.1101/gr.306102